The crime of embezzlement of public funds Dogmatic and political-criminal considerations - Pariona Arana, Raúl (2019)
This article develops a brief account of the evolution of the crime of Embezzlement of Public Funds in Peru, as well as regulation in other countries. Finally, it comments widely on the legal right, the subjective elements, objectives of the type and the degrees of participation of the aforementioned crime.